Pergulatan Pemikiran Teologi di Dunia Islam - Alkhendra Alkhendra (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2015)
The word theology comes from the English term, namely theology. In language means the science of divinity. The term used in the English, initially also taken from the Greek word, which is from the root word theos meaning God, and logos meaning science. In the science study of Kalam, the term theology is also known as another name of theology itself. The difference, the term theology is a term commonly used by Western literature, especially English, to mention theology in Islam, while the term theology is a term commonly used by literature- literature East (Arabic). If so, theology in the context of Islam can be understood as a discipline that talks about the problems of divinity or theology is nothing other than itself.